Perbandingan Efektivitas Antibiotik Thiamfenikol dan Ofloksasin pada Demam Tifoid Pasien Rawat Jalan Di RS Panti Waluyo Purworejo - Lucia Vita Inandha (Fakultas Farmasi Universitas Setia Budi, 2011)
Typhoid fever is one of the bacterium infections frequently found in many developing countries including Indonesia. The case also occurs in Purworejo based on the data obtained from Panti Waluyo Hospital, Purworejo. The hospital mostly use thiampenicol and ofloxacin antibiotics for the medication of it. The research project was aimed to recognizing the efficacy of them based on the result of clinical observation toward the patients after taking the antibiotics. The research was conducted using prospective experimental method on the patients in the on going care installation in Panti Waluyo Hospital Purworejo. They had been diagnosed as having typhoid fever. The research subjects were divided into two groups: 25 subjects got 500 mg thiamphenicol antibiotic wich was taken three times a day, the other 25 subjects got 200 mg ofloxacin taken twice a day. The observation was done since the first day the patients took the medicine until their subsequent visit for the check-up. The clinical result of the patient were noted and investigated to see how many days the fever and other clinical symptoms finally came to an end after taking the antibiotics. The result demonstrated that the means of the end of the fever for the patients who had taken thiampenicol occured on day 3.44, whereas the means of the end of the fever for the patients who had taken ofloxacin occured on the second day. The statistical analysis reveals that there is a significant difference between the two antibiotics regarding the end of the fever. The means of other clinical symptoms concerning the typhoid fever for the patients who had taken thiampenicol occured on day 3.16, whereas the means of these symptoms for the patients who had taken ofloxacin occured on day 3.08. The statistical analysis demonstrates that there is no significant difference toward the duration of the end of other clinical symptoms generated by both antibiotics.